Bulimia Symptoms in Russian Youth: Prevalence and Association With Internalizing Problems - Koposov, Roman A.; Stickley, Andrew; Ruchkin, Vladislav (Frontiers in Psychiatry, 2022)
Background: There has been limited research on bulimia symptoms in adolescents from the general population outside the United States. This study aimed to evaluate the prevalence of bulimia symptoms in Russian youth and explore the associations between a clinical level of self-reported probable bulimia nervosa (BN) and internalizing problems, binge drinking and functional impairment by gender. Methods: Data were collected from a representative sample of school students (N=2515, 59.5% female) from Northern Russia (M (SD)=14.89±1.13 years). Probable BN and internalizing psychopathology were assessed using self-report scales. Chi-square and independent sample t-tests were used to compare respondents’ demographic characteristics. GLM multivariate analysis of covariance was used to assess the associations between probable BN, functional impairment and mental health problems (MHP) by gender. Results: Analyses showed that the 3-month prevalence of probable BN was higher in girls (3.9%) than in boys (1.2%). Probable BN was associated with depressive and anxiety symptoms, somatic anxiety, somatic complaints, binge drinking and functional impairment. Boys reported a higher level of problem scores in relation to probable BN. Conclusions: Our findings suggest that bulimia symptoms are prevalent in Russian adolescents and are associated with MHP and functional impairment. Timely recognition of bulimia symptoms and associated MHP is important for early prevention and intervention strategies.